Assessment of levels of plasma oxidative stress in patient having aggressive periodontitis before and after full mouth disinfection - Sachin Bhagat; Parthivi Singh; Anuj Singh Parihar; Gurpreet Kaur; Harsh Takkar; Rathi Rela (Wolters Kluwer Medknow Publications, 2021)
Aim: The primary purpose of the study was to evaluate the levels of oxidative stress in plasma in patients with aggressive periodontitis (AgP) before and after full-mouth disinfection. Materials and Methods: Twenty-five healthy controls and 25 participants with aggressive periodontal were assessed for plaque index, probing pocket depth, papillary bleeding index, and clinical attachment level. Periodontal bone support was assessed by taking full mouth periapical radiographs. Full-mouth disinfection of the patient was done within 24 h of clinical assessment of AgP. These parameters were assessed at the baseline and after 8 weeks of initial periodontal therapy. Plasma samples were taken and evaluated for various oxidative stress markers. Results: Strong positive correlation was observed among periodontal parameters and levels of enzymatic/nonenzymatic biomarkers for oxidative stress (thiobarbituric acid-reactive substances [TBARS], glutathione peroxidase [GPX], and catalase [CAT]) (P < 0.05), before and after periodontal management. The patients with AgP had high levels of TBARS, GPX, and CAT levels in the plasma matched to the healthy individuals (P < 0.05). Conclusion: Enzymatic and nonenzymatic oxidative stress may have a role in the pathogenesis AP. Initial periodontal treatment can lead to the reduction of these stresses.